2006
DOI: 10.1021/jf0617925
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of the Phenolic Fraction of Spanish Virgin Olive Oils by Capillary Electrophoresis with UV Detection

Abstract: A rapid and reliable capillary zone electrophoresis method was used as a tool to obtain both qualitative and quantitative information about simple phenols, lignans, complex phenols (isomeric forms of secoiridoids), phenolic acids, and flavonoids in the solid-phase separation extracts from different Spanish extra-virgin olive oil in a short time (less than 6 min). Peak identification was done by using commercial and HPLC-isolated standards, studying the information of the electropherograms obtained at several w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 30 publications
1
34
0
4
Order By: Relevance
“…ARB, HOJ and PIC (Gorinsteina et al, 2003), different findings were reported by other researchers (Carrasco-Pancorbo et al, 2006;García et al, 2003). García et al (2003) found significant differences for total and individual polyphenol or tocopherol contents, for the same three ES olive cultivars.…”
Section: Spanish Monovarietal Evoo Discriminationmentioning
confidence: 63%
See 1 more Smart Citation
“…ARB, HOJ and PIC (Gorinsteina et al, 2003), different findings were reported by other researchers (Carrasco-Pancorbo et al, 2006;García et al, 2003). García et al (2003) found significant differences for total and individual polyphenol or tocopherol contents, for the same three ES olive cultivars.…”
Section: Spanish Monovarietal Evoo Discriminationmentioning
confidence: 63%
“…Previously, the use of hydro-methanolic mixtures was already reported to overcome this issue (Rodríguez-Méndez, Apetrei, & de Saja, 2008). These alcoholic extracts are expected to be rich in polar compounds, such as sterols, polyphenols and tocopherols, which differ considerably among olive oils cultivars and are the main contributors to olive oil bitterness, astringency and pungency (Apetrei et al, 2010;Carrasco-Pancorbo et al, 2006;García, Brenes, Garcí, Romero, & Garrido, 2003;García, Brenes, Romero, García, & Garrido, 2002;Matos et al, 2007;Morelló, Romero, & Motilva, 2004;Romero, & Brenes, 2012). Therefore their use as suitable discriminating descriptors was investigated, since it is expected that those compounds (e.g., sterols, polyphenols and tocopherols) are the major constituents of the hydro-ethanolic extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil organoleptic attributes [1,[4][5][6] and physicochemical parameters [7,8] are important for olive oil quality assessment and discrimination, avoiding the indiscriminate use of uncorrected definitions in olive oil labels [1]. These analysis are time-consuming and costly, requiring trained sensory panelists and high-skilled technicians, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid aglycones are subdivided into flavones, flavonols, flavanones, and flavanols depending upon the presence of a carbonyl carbon at C-4, an OH group at C-3, a saturated single bond between C-2 and C-3, and a combination of no carbonyl at C-4 with an OH group at C-3, respectively. Several authors have reported that flavonoids such as luteolin and apigenin are also phenolic components of VOO [41][42][43][44][45][46]. Luteolin may originate from rutin or luteolin-7-glucoside, and apigenin from apigenin glucosides.…”
mentioning
confidence: 99%